Awakening the essence of classroom community building. (December 2022) - Acosta, Melanie M; Woodard, Paul
In continuing the legacy of community-mindedness, good Black educators today consistently enact emancipatory pedagogies designed to protect Black children's personhood. Cultivating community in the classroom setting is one ritual they use toward affirming young Black children's literate character, presence, and pursuits, and they do so in the midst of constant disruption to Black children's language and literacy development imposed by eurocentric curriculum and instruction. This Afrocentric case study, or Afronography, draws on dialogic discussions and video-recorded teaching sessions to examine the classroom community-building practices of one African American woman educator during her literacy instruction with Black third graders. Data analysis revealed that the teacher created opportunities for her Black students to increase their sense of belonging in the classroom.